Antifungal potential of thyme essential oil as a preservative for storage of wheat seeds - Anzlovar, Sabina; Likar, Matevz; Dolenc Koce, Jasna (Acta Botanica Croatica, 2017)
Plant essential oils are potential food preservatives due to their inhibitory effects on bacterial and fungal growth. Antifungal activities of common thyme (Thymus vulgaris) essential oil were tested against endophytic fungi grown from wheat (Triticum aestivum) grain, molecularly identified as Alternaria alternata, Alternaria infectoria, Aspergillus flavus, Epicoccum nigrum and Fusarium poae. Their susceptibility to thyme essential oil was tested in vitro, and ranged from fungicidal to fungistatic. Treatment combinations of prior grain surface sterilization with hypochlorite and direct/indirect treatment with the essential oil were used, which showed strong effects on infection incidence and germination. Direct soaking of the wheat grain in the essential oil was particularly effective, but inhibited both fungal growth and seed germination. In contrast, indirect treatment of the grain with the essential oil (i.e., fumigation) inhibited fungal growth without negative effects on seed germination. In combination with grain surface sterilization with hypochlorite, indirect treatment with thyme essential oil reduced these fungal infections even more. Since thyme essential oil is safe for plants and consumers, in the form of fumigation it could be used as a protectant of storage containers for wheat grain intended for sowing and for food production.